Empowering Gen Z Learning: Wordwall-Based Educational Game Development in Differentiated Instruction for Elementary Students - Agustina, Livia; Fitriani, Somariah; Fatayan, Arum (Mimbar Sekolah Dasar, 2025)
This study aims to develop wordwall-based educational game media for the sixth-grade elementary students in learning the human skeletal system. In addition, this study is intended to explore students’ perspectives of the use of such developed media. This research development research design employed the Four-D model to guide the development process and a single case study design to explore the students’ perspectives and learning experiences on the use of developed media. The sixth-grade students of public primary school in Jakarta, Indonesia participated in the study. Data were garnered through observation, questionnaires, pretest and post-test, and interviews. The first finding reported the effectiveness of developed media from significant pretest-post-test improvements, with a mean final score of 79.6, surpassing the minimum competency standard, which is 73.  The second finding indicated that the wordwall educational game media can accommodate students’ auditory, kinesthetic and visual learning styles. In addition, the interviews revealed that the use of wordwall platform is aligned with students’ interest, readiness to learn and learning profile as the principles of differentiated instruction. The study concludes that innovative learning media, such as wordwall-based educational games, makes learning interactive and enjoyable as well as facilitates differentiated instruction.